Evaluating Coordination Practices and Employee Performance in Local Government Organizations: Evidence from Indonesia - Ade Setiadi (Sultan Publisher, 2024)
Effective coordination is vital for the efficiency of an organization and the improvement of employees’ performance in public sector institutions. The objective of this study was to measure the performance of the employees and the coordination practices of the Department of Education and Culture of Indramayu Regency, Indonesia. This study employed descriptive quantitative research design with census of 54 employees as research participants. Data were collected using structured questionnaire and analyzed using descriptive statistics. The research instrument was tested for validity and reliability. The results indicated that coordination practices were generally perceived as good with a mean score of 3.74. Considering the dimensions of coordination, the conferences were rated the highest, and the forums the lowest. This indicates areas for improvement in employee involvement in organizational coordination. The performance of employee was also rated as good with an overall mean score of 4.04 indicating positive performance of employee in terms of indicators of work quality, work quantity, cooperation, initiative and responsibility. The study concludes that within the organization effective coordination mechanisms have been implemented and that the sustainability of participatory coordination practices could promote continuous organizational improvement and improve the quality of public administration.